The Translation Of Complex Sentences In “Cantik Itu Luka” Novel - Orlando, Alexander Goldy; Utami, Ni Made Verayanti; Maharani, Putu Devi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the sentence structures found in the novel and the acceptability of their translations in the target language. The data were collected through direct observation and analyzed using a descriptive qualitative method. The study was conducted because English exposure in countries where English is not the native language does not guarantee that people can fully understand and use it accurately. The analysis identified seven intentional complex sentences that were translated into corresponding complex sentences in the English version of the novel. The original author predominantly used the subordinators “untuk” and, in several parts, “agar.” In the English translation, a variety of subordinators were employed to maintain grammatical and contextual equivalence. The structural distribution shows that Independent–Dependent constructions appeared in 75% of the data, while Dependent–Independent constructions accounted for 25%. This indicates that the translator generally preferred maintaining the source text’s syntactic pattern, ensuring readability and coherence in the target language. Based on the questionnaire responses, approximately 88% of the translated complex sentences were considered easily understood by respondents, indicating high translation acceptability. However, according to Larson’s (1984) theory of Translation Acceptability, two sentences failed to meet the acceptability criteria due to minor issues in meaning equivalence and naturalness. Overall, the findings highlight the importance of syntactic and semantic accuracy in literary translation to preserve the author’s intent and maintain fluency in the target language, especially when translating complex sentence structures across linguistically distant languages.